A QBO Cookbook: Sensitivity of the Quasi‐Biennial Oscillation to Resolution, Resolved Waves, and Parameterized Gravity Waves. (22nd March 2022) - Garfinkel, Chaim I.; Gerber, Edwin P.; Shamir, Ofer; Rao, Jian; Jucker, Martin; White, Ian; Paldor, Nathan
Abstract: An intermediate complexity moist general circulation model is used to investigate the sensitivity of the quasi‐biennial oscillation (QBO) to resolution, diffusion, tropical tropospheric waves, and parameterized gravity waves. Finer horizontal resolution is shown to lead to a shorter period, while finer vertical resolution is shown to lead to a longer period and to a larger amplitude in the lowermost stratosphere. More scale‐selective diffusion leads to a faster and stronger QBO, while enhancing the sources of tropospheric stationary wave activity leads to a weaker QBO. In terms of parameterized gravity waves, broadening the spectral width of the source function leads to a longer period and a stronger amplitude although the amplitude effect saturates in the mid‐stratosphere when the half‐width exceeds ∼ 25 m/s. A stronger gravity wave source stress leads to a faster and stronger QBO, and a higher gravity wave launch level leads to a stronger QBO. All of these sensitivities are shown to result from their impact on the resultant wave‐driven momentum torque in the tropical stratosphere. Atmospheric models have struggled to accurately represent the QBO, particularly at moderate resolutions ideal for long climate integrations. In particular, capturing the amplitude and penetration of QBO anomalies into the lower stratosphere (which has been shown to be critical for the tropospheric impacts) has proven a challenge. The results provide a recipe to generate and/or improve the simulation of the QBO in an atmospheric model. Plain Language Summary: The most prominent mode of variability in the tropical stratosphere is the quasi‐biennial oscillation (QBO), characterized by easterly and westerly winds alternating sign every ∼ 14 months. Only relatively recently have comprehensive models begun to simulate a QBO spontaneously, and even in these models the representation of the QBO typically suffers from biases. Here we elucidate the sensitivities of the QBO to a wide range of model parameters, and explore how these parameters affect the QBO behavior. We expect that these results will be helpful for improving the QBO in more comprehensive models. Key Points: Sensitivity of the quasi‐biennial oscillation (QBO) to resolution, dissipation, wave forcing, and parameterized gravity waves is explored in a single framework The influence of these factors on the QBO can be related to their impact on wave‐induced momentum fluxes in the deep tropics The QBO period can be tuned independently of its amplitude, but the vertical structure (particularly at lower levels) is harder to capture